The Syntactic Profile of Nepali Ergativity - Lindemann, Luke (Nepalese Linguistics, 2024)
Ergative case-marking in Nepali is syntactically shallow even compared to other Indo-Aryan languages. The structure of ergative case-marking in Nepali is examined in the context of structural, inherent, and dependent theories of case assignment, and in particular Legate’s typology of Inherent case and the Marantz Case Generalization, and it is determined that a dependent case theory best describes the Nepali pattern.